Effects of Storage Period and Insecticidal Dusts on Wheat Seed Quality - RAJESH KHOSLA; B.S. CHHILLAR; R.K. KASHYAP (Seed Research, 2026)
Six insecticidal dusts viz., fenvalerate 0.4D, methyl parathion 2D, endosulfan 4D, quinalphos 1.5D, malathion 5D and carbaryl 5D each @ 1.5, 2.5 and 3.5g/kg seed were mixed with wheat (cv. Raj-3765) seeds to evaluate their effect on seed quality up to 180 days under ambient storage conditions at Hisar. Fenvalerate 0.4D, malathion 5D and endosulfan 4D did not adversely effect the germination, whereas methyl parathion 2D and quinalphos 1.5 D (both @ 2.5 and 3.5g/kg seed) deteriorated the seed germination. All the doses of carbaryl 5D were comparable to untreated seeds for standard germination. Seedling vigour improved by fenvalerate 0.4D, endosulfan 4D and malathion 5D treatments, whereas all the doses of methyl parathion 2D, quinalphos 1.5D and carbaryl 5D reduced vigour as compared to control. Storage period of insecticide treated seed had linear relationship with deterioration of seed quality.